Toponyms “Russia”, “Moscow”, “Barnaul” in the Minds of Chinese Students - Lidiya M. Dmitrieva (Transbaikal State University, 2021)
The article analyzes the toponyms “Russia”, “Moscow” and “Barnaul” from the point of view of the mental toponymic stereotype in the minds of Chinese students. The aim of the study is to identify the origin of these toponyms, as well as their perception in the minds of Chinese students. The difference in culture and ethnicity makes it inevitable for people who come into contact with the culture of other countries or other ethnic groups to develop stereotypes. So, further study of toponyms associated with the history and culture of Russia will expand the circle of knowledge of Chinese students about Russian culture. The study is based on the results of a survey of 100 Chinese students in order to identify their understanding and identify stereotypes regarding the geographical names “Russia”, “Moscow” and “Barnaul”. A consistent study of toponyms will help to achieve their understanding. The use of the questionnaire method and associative experiment made it possible to reveal the influence of existing stereotypes among Chinese students in the understanding of foreign (Russian) toponyms “Russia”, “Moscow”: and “Barnaul”. The understanding by foreign students of geographic names that are not nationals is always primarily related to the geographic location in which they are located and some of the features for which the city is famous. In this regard, the impression that Moscow is red is deeply rooted in the minds of Chinese students. Thus, the authors come to the conclusion that toponyms carry an unprecedented amount of information related to historical and socio-cultural aspects. Russian toponyms can help Chinese students learn more about Russian culture and expand their understanding of it. In order to understand the names of Russian toponyms, Chinese students rely on their geographical location, climate, features of the national language and culture, as well as on the study and understanding of various cultural symbols.